MODEL PEMBELAJARAN TEAM GAMES TOURNAMENT MATERI BILANGAN BULAT - Azmi Aqil; Zubaidah R; Ahmad Yani T (UNIVERSITAS TANJUNGPURA, 2021)
This study aims to explain and describe the effectiveness of the Team Games Tournament (TGT) type cooperative learning model conducted in class VII SMPN 1 Sungai Raya. The method used in this research is descriptive-quantitative. The results obtained from this study are TGT type of cooperative learning is effective enough to be applied to the material integer count operations in SMPN 1 Sungai Raya this can be seen fromThe implementation of the teacher in managing cooperative learning type TGT is in the very good category with an average score of 3.73, the learning activities of students during learning using the type GI cooperative learning are in the active category with a percentage of 89.2%, the response of students to the application of cooperative learning type TGT is in the positive category and the learning outcomes of students have reached ketstrand classical because 81% of students have reached the KKM. Keyword: TGT, Effectiviness, SMPN 1 Sungai Raya